Hiperactividad : ¿Síntoma o trastorno? ¿De qué o de quién? (2009)
ABSTRACT: One of present "the symptomatic" manifestations with more welcoming, use, abuse and sobrediagnosis are the Hiperactividad call or upheaval with attention deficit (TDAH). The investigation made in a school specialized in this upheaval shows clearly the little effectiveness of the farmacológico and comportamental treatment applied the children and "affected" young people by this diagnosis. The closed logic school-professionals and drug is a practice common in the present time that the interrogation by the sense excludes and meaning that this symptom represents for the subject in its relation the Other. For the Psychoanalysis this it is the axis of his intervention, to interrogate that subject it is put into play in that symptom and that function has for him.